2018
DOI: 10.3892/etm.2018.6049
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of heme oxygenase‑1 protected against brain damage induced by transient cerebral ischemia‑reperfusion injury in rats

Abstract: The aim of the present study was to identify the effect of heme oxygenase (HO)-1 gene on cerebral ischemia-reperfusion injury. Sprague-Dawley rats were divided randomly into four groups: Sham group, vehicle group, empty adenovirus vector (Ad) group and recombinant HO-1 adenovirus (Ad-HO-1) transfection group. Rats in the vehicle, Ad and Ad-HO-1 groups were respectively injected with saline, Ad or Ad-HO-1 for 3 days prior to cerebral ischemia-reperfusion injury. Subsequently, the middle cerebral artery occlusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…For example, it has been previously reported that neuronal expression of HO-1 is usually detected in rodent brains challenged with anoxic stimuli, including hypoxia or oxidative stress [41]. Furthermore, genetically engineered HO-1-deficient mice exhibit exaggeration in ischemic damage when compared to wild type controls [42,43]. Together with the results of this study, these findings suggest that PSL possesses a powerful neuroprotective effect, which may be effective against cerebral ischemia via upregulation of HO-1.…”
Section: Discussionsupporting
confidence: 79%
“…For example, it has been previously reported that neuronal expression of HO-1 is usually detected in rodent brains challenged with anoxic stimuli, including hypoxia or oxidative stress [41]. Furthermore, genetically engineered HO-1-deficient mice exhibit exaggeration in ischemic damage when compared to wild type controls [42,43]. Together with the results of this study, these findings suggest that PSL possesses a powerful neuroprotective effect, which may be effective against cerebral ischemia via upregulation of HO-1.…”
Section: Discussionsupporting
confidence: 79%
“…However, DHE is also easily oxidized by heme peroxidases. In the ischemic brain, heme peroxidase is elevated and released, which leads to an increase in ROS formation when monitored by ROS-sensitive fluorescent probes (Kim et al, 2016;Lu et al, 2018). To complement this, there are ongoing attempts to develop a new generation of ROS probes to measure ROS activity in vivo.…”
Section: Pur Restored Levels Of Shh Signaling After Himentioning
confidence: 99%
“…More importantly, a growing number of researches have corroborated that EMO might be a neuroprotective agent for remedy nervous system diseases [17,25]. Cerebral ischemia injury belongs to central nervous system (CNS) injury, which gives rise to irreversible brain damage and even neurological sequelae [26]. Hence, our research attempted to further disclose whether EMO emerges the protective action in cerebral ischemia injury.…”
Section: Discussionmentioning
confidence: 95%